(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
Johann J. Hagen, Die Anklagen gegen Andokides: Ein Rekonstruktionsversuch, Hamburg, Verlag Dr. Kovač, 2021, 424 S. ISBN: 978-3-339-12522-4